2004
DOI: 10.1074/jbc.m411049200
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of JNK Signaling by the Tumor Suppressor CYLD

Abstract: CYLD is a tumor suppressor that is mutated in familial cylindromatosis, an autosomal dominant predisposition to multiple tumors of the skin appendages. Recent studies suggest that transfected CYLD has deubiquitinating enzyme activity and inhibits the activation of transcription factor NF-B. However, the role of endogenous CYLD in regulating cell signaling remains poorly defined. Here we report a critical role for CYLD in negatively regulating the c-Jun NH 2 -terminal kinase (JNK). CYLD knockdown by RNA interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
1
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 51 publications
9
102
1
2
Order By: Relevance
“…Dysregulation of both classes of NF-kB targets would be expected to participate in cylindroma formation. Nevertheless, it cannot be ruled out that effects on other signaling pathways, which are under CYLD control, such as the c-Jun N-terminal kinase pathway (Reiley et al, 2004), also play a role in cylindromatosis.…”
Section: Ikba-related Immune Deficiencymentioning
confidence: 99%
“…Dysregulation of both classes of NF-kB targets would be expected to participate in cylindroma formation. Nevertheless, it cannot be ruled out that effects on other signaling pathways, which are under CYLD control, such as the c-Jun N-terminal kinase pathway (Reiley et al, 2004), also play a role in cylindromatosis.…”
Section: Ikba-related Immune Deficiencymentioning
confidence: 99%
“…Studies have shown that ER stress promotes NF-kB-dependent activation of TNFa expression via association of IKK with the ER stress sensor IRE1a and TRAF2, whereas simultaneous downregulation of TRAF2 impairs activation of NF-kB and JNK greatly potentiates the toxic effect of TNFa (Hu et al, 2006a). Another way in which NF-kB can enhance cell death is via upregulation of the tumor suppressor CYLD that acts as a deubiquitinase to remove K63 polyubiquitin chains from TRAF2/6 and NEMO, leading to disassembly of the IKK complex, termination of NF-kB signaling and enhanced cell death (Brummelkamp et al, 2003;Kovalenko et al, 2003;Jono et al, 2004;Reiley et al, 2004). CYLD also deubiquitinates the p50 and p52 coactivator Bcl-3 to suppress activation of genes that promote cell proliferation and tumor growth (Ikeda and Dikic, 2006;Massoumi et al, 2006).…”
Section: Mechanisms Implicated In Nf-kb's Proapoptotic Activitymentioning
confidence: 99%
“…It has been recently shown to be under CYLD control, via the effect of this deubiquitinase on TRAF2 or TRAF6. 73 Therefore, cylindromatosis is unlikely to be a 'pure' NF-kB-related pathology.…”
Section: Familial Cylindromatosis and Multiple Familial Trichoepithelmentioning
confidence: 99%